Crime, incentives and political effort: A model and empirical application for India - Kai Gehring; Florian Kauffeldt; Krishna Chaitanya Vadlamannati (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
We develop a model of the incentives faced by members of parliament (MPs) when deciding whether to engage in effort for their constituencies to assess the effects of their having a criminal background. Political representatives with criminal backgrounds are considered a great problem in many countries. In particular in India, a public disclosure revealed that a large proportion of politicians currently face criminal charges. This has led to a heated public debate and emerging literature assessing the causes and effects of this disturbing phenomenon. We use a comprehensive set of three proxies to measure effort in the 14th Lok Sabha over the 2004-2009 legislative period: attendance rates, parliamentary activity, and utilization rates of a local area development fund. We find that MPs facing criminal accusations exhibit on average about 5% lower attendance rates and lower fund utilization rates, and less (but insignificantly) parliamentary activity. As predicted by the model, these differences depend on the development level of the constituency, a proxy for rent-seeking possibilities and monitoring intensity. We argue and demonstrate why these negative relations should constitute an upper bound estimate of the causal effect, and show that even under conservative assumptions the effect is unlikely to be caused by unaccounted selection-bias.
Keywords: D72; H11; I38; 330; India; Elections; Crime; Good and bad politicians; Development; Attendance and activity in parliament; Political economy